Evaluation of Antioxidant and Antibacterial Potentials of Nigella sativa L. Suspension Cultures under Elicitation. (12th August 2015) - Chaudhry, Hera; Fatima, Nida; Ahmad, Iffat Zareen
Abstract : Nigella sativa L. (family Ranunculaceae) is an annual herb of immense medicinal properties because of its major active components (i.e., thymoquinone (TQ), thymohydroquinone (THQ), and thymol (THY)). Plant tissue culture techniques like elicitation, Agrobacterium mediated transformation, hairy root culture, and so on, are applied for substantial metabolite production. This study enumerates the antibacterial and antioxidant potentials of N. sativa epicotyl suspension cultures under biotic and abiotic elicitation along with concentration optimization of the elicitors for enhanced TQ and THY production. Cultures under different concentrations of pectin and manganese chloride (MnCl2 ) elicitation (i.e., 5 mg/L, 10 mg/L, and 15 mg/L) showed that the control, MnCl2 10 mg/L, and pectin 15 mg/L suspension extracts greatly inhibited the growth of E. coli, S. typhimurium, and S. aureus (MIC against E. coli, i.e., 2.35 ± 0.8, 2.4 ± 0.2, and2.46 ± 0.5, resp.). Elicitation decreased SOD enzyme activity whereas CAT enzyme activity increased remarkably under MnCl2 elicitation. MnCl2 10 mg/L and pectin 15 mg/L elicitation enhanced the DPPH radical inhibition ability, but ferric scavenging activity was comparable to the control. TQ and THY were quantified by LC-MS/MS in the cultures with high bioactive properties revealing maximum content under MnCl2 10 mg/L elicitation. Therefore, MnCl2 elicitation can be undertaken on large scale for sustainable metabolite production.